Model sistem audit kewangan sekolah - Ismail Khalid, Gadar Kamisan, Saad Norizan, Ahmad Mohamad Ali Roshidi, (Universiti Pendidikan Sultan Idris, 2008)
Model sistem audit kewangan sekolah by Ismail Khalid, Gadar Kamisan, Saad Norizan, Ahmad Mohamad Ali Roshidi,